2018
DOI: 10.14744/semb.2018.09582
|View full text |Cite
|
Sign up to set email alerts
|

The association between migraine, metabolic syndrome, insulin resistance, and obesity in women: Case-control study

Abstract: M igraine headache is a complicated, repetitive headache disorder that is a very pervasive complaint in neurology. The overall prevalence is 5% to 15%, [1, 2] and it is more frequent among females than males. [3] Migraines are thought to be related to various comorbid disorders, such as epilepsy, depression, anxiety, ischemic stroke, Raynaud's phenomenon, iron deficiency anemia, obesity, insulin resistance (IR), and metabolic syndrome. [4-6] However, the relationship between migraines and these comorbid disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Thus, the higher levels of plasma UFAs in CM may suggest an enhanced activation of lipolytic pathways. Since the balance of glucagon/catecholamines and insulin controls lipolysis, insulin resistance is suggested to be associated with migraine pathophysiology ( Fava et al, 2014 ; Ozcan and Ozmen, 2019 ) may also account for the higher levels of UFAs in CM plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the higher levels of plasma UFAs in CM may suggest an enhanced activation of lipolytic pathways. Since the balance of glucagon/catecholamines and insulin controls lipolysis, insulin resistance is suggested to be associated with migraine pathophysiology ( Fava et al, 2014 ; Ozcan and Ozmen, 2019 ) may also account for the higher levels of UFAs in CM plasma.…”
Section: Discussionmentioning
confidence: 99%
“…We summarize the implication of these changes in Table 2 . The physiological implications include energy production ( Lindsay, 1975 ; Jumpertz et al, 2012 ; Nakamura et al, 2014 ; Alcock and Lin, 2015 ; Cucchi et al, 2019 ), the trigger of the inflammatory response through via TLR4 signaling pathway associated with pain pathogenesis ( Zhang and Ma, 2017 ), worsening pain ( Sekar et al, 2020 ), and a link to insulin resistance that is proposed to be a part of migraine pathophysiology ( Rao and Pearce, 1971 ; Perciaccante and Perciaccante, 2008 ; Bhoi et al, 2012 ; Ozcan and Ozmen, 2019 ). The levels and de novo synthesis of SAFAs are linked with CNS and peripheral nervous system myelination ( Salles et al, 2002 ; Montani et al, 2018 ; Dimas et al, 2019 ), and fatty acid elongation is increased during active myelination in rodents ( Morita et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance (IR) has been proposed as an underlying pathophysiological mechanism involved in the association between migraine and diabetes ( 173 ), although not all studies found this link ( 174 ). Migraine patients have been reported to have increased insulin levels compared to controls ( 175 , 176 ).…”
Section: Association Between Migraine and Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…16 Low levels of vitamin D have been shown to increase the risk of various health conditions, including metabolic disorders, autoimmune diseases, and cardiovascular diseases 17,18 . Research has suggested a possible association between migraine and low levels of vitamin D 19 , hypercholesterolemia, high blood glucose 5 , hypertension 20 , insulin resistance, diabetes 21 , anthropometric measurements, including body mass index (BMI) and waist circumference. 22,23 However, the association between migraines is not well established, and further research is required to determine the exact mechanism underlying this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a study indicated that insulin resistance and metabolic syndrome were not associated with migraine in women and was an inverse relationship between central obesity and migraine. 21 Most studies involving the migraine have been performed in predominantly populations if aged mean of 40-60 years. Little is known about the involving young women, especially Brazilian young women.…”
Section: Introductionmentioning
confidence: 99%